A Project Report on Simulation Study of HVDC Power System - ANURADHA N,ASHARANI N,BABKAN MARY and HEMARATHI (2006)
INTERNAL GUIDE: SUSHMITHA SARKAR M VJCE EXTERNAL GUIDE:GHAMANDI LAL SENIOR MANAGER BHEL
Keywords: A Project Report on Simulation Study of HVDC Power System